Analisis Pemilihan Moda Transportasi Di Pasar Hewan Menggunakan Model Logit Biner( Studi Kasus: Pasar Hewan Desa Purworejo Kecamatan Nogosari) - Dewi, Dhiyan Kartika; , Nurul Hidayati, ST., MT., Ph.D; , Drs. Gotot Slamet M, MT (2017)
In Nogosari, there is actually a fairly large animal market, but its existence only crowded on certain days (called the Market). Animals sold in this market consist of cows and goats delivered from various regions. Selection modes for transporting animals affected by animal type, and number of animals to be transported, as well as the carrying capacity of the vehicle. This study aims to identify the characteristics and factors that can affect the modal choice and also create the model. This study used interviews survey respondents. Respondents were taken consisted of sellers and buyers in this market. The method used to analyze is binary logic model. The analysis showed that the majority of buyers and sellers were male (91.4%), and aged between 30 years to 50 years. Transportation modes most widely used are trucks (56.4%), with most of the animals were transported cows (65.7%). Most of the vehicles used are the personal vehicle of the respondents, with the closest distance is 0.5 km. Components of transport costs are influenced by the cost of porters (Rp 3000.00 - Rp 100,000.00), and the amount of fuel used (1 liter - 20 liters). The obtained modal choice models are: P1 = and P1 = .